Die Freimaurer im Alten Preußen 1738-1806, Die Logen zwischen mittlerer Oder und Niederrhein Die Logen zwischen mittlerer Oder und Niederrhein - Gerlach, Karlheinz (Studien Verlag, 2007)
In the centre of the present research on the social history of the Prussian freemasonry in the 18 century are the history of the lodges, the membership and its structure, the social and cultural life of the lodges and their influence on society, i.e. the actual societal situation of the lodges in the late feudal society of Brandenburg-Prussia towards the end of the Early Modern Age. The ideological aims and practice of the systems of freemasonry (rituals etc.), the philosophical and literary critique as well as the arts rooted in freemasonry are delt with only in passing.The sources of this research are the traditional manuscripts from archives, mostly unique old scripts and modern masonic literature, as well as the literature of socio-historical, regional-historical and biographical origin. The following sources have been searched and analyzed: the opulent masonic sources of the ancient Prussian lodges of the Geheimes Staatsarchiv Preußischer Kulturbesitz, Berlin-Dahlem, having been made available since 1990; the sources of the Orde van vrijmetselaren onder het Grootoosten der Nederlanden, Den Haag, of the Den danske Frimurerorden, Kopenhagen, of the Landesarchiv Berlin, of the Landesarchiv Magdeburg - Landeshauptarchiv, the Brandenburgisches Landeshauptarchiv, Potsdam, the Stadtarchiv Potsdam, the Thüringisches Hauptstaatsarchiv, Weimar, the Österreichisches Staatsarchiv, department Haus-, Hof- und Staatsarchiv, Vienna, as well as the libraries of the Deutsches Freimaurer-Museum, Bayreuth, the Great Lodge of Freemasons of Germany, Berlin, the Great National Mother Lodge "To the Three Globes" in Berlin, the Biblioteka uniwersytecka w Poznaniu, Pracownia Zbiorów Masonskich, Poznan, and the Great Lodge of the Old Free and Accepted Freemasons of Austria, Vienna.The Handbook is structured chronologically according to regions and with analogue topics; the alphabetic commented lists of the entire membership follow the chapters of every lodge. Regionally the research covers the Prussian states within their borders of 1795 (Peace of Basel, Third Polish Partition), but without territories that followed a relative autonomous way in their history, or belonged to Prussia only a short term, or came to Prussia after 1795. This manuscript deals with Prussian lodges between the Oder river and the Lower Rhine; the envisaged volumes for publication will include Berlin, Pomerania, Eastern and Western Prussia as well as Silesia.The favourable policy of the Prussian kings formed the external political basis for a continuous development of the freemasonry in the monarchy. This began 1740 with the legitimation of the freemasons by Frederic II and led to the "Common Law of the Prussian States" and the following "Edict on Secret Associations" in 1798.Between 1739 and 1806, 47 legally constituated Johannis lodges as parts of the larger Lodges have been registered in 30 towns in the middle and western provinces, but without Berlin. Until the Seven Year War (1756-1763) the small number of isolated lodges was restricted to the larger cities. A stimulating influence for the freemasonry came only from the garnisons (lodges of the captured officers). After the war, during a long peaceful period, the freemasonry took a steep upsurge, despite the internal struggles, called the "Lodge Wars", and the splittings. The freemasonry extended over the entire country, to the big cities and medium-sized towns and many rural towns.The Lodges distinguished themselves from other associations by their social openness and broadth of membership. They organized a rising number of men from different classes, social strata, groups or trades, (christian) confessions, education and ages. The freemasons belonged to the newly emerging social strata and groups which formed the Prussian state of Frederic II and were closely connected with its progress. These were the nobility and the middle class, the clerks and officers, bankers and manufacturers, intellectuals and artists. The